Answer:
b = -5
Explanation:
Let's figure this equation, step by step.
-3b + 8 = 38 + 3b
Step 1: Subtract 3b from both sides. This cancels out the addition by 3b.
-3b + 8 - 3b = 38
Step 2: Combine -3b and -3b to get -6b.
-6b + 8 = 38
Step 3: Subtract 8 from both sides. This cancels out the addition by 8.
-6b = 38 - 8
Step 4: Subtract 8 from 38 to get 30.
-6b = 30
Step 5: Divide both sides by -6. This undoes the multiplication by -6.
b = 30/-6
Step 6: Divide 30 by -6 to get -5.
b = -5
Let's check our work by substituting -5 for b in the equation above.
-3(-5) + 8 = 38 + 3(-5)
15 + 8 = 38 + (-15)
23 = 23
Both sides are the same, so b = -5.